The Interactions Between Cancer Stem Cells and the Innate Interferon Signaling Pathway - Martin-Hijano, Laura; Sainz, Bruno (Frontiers in Immunology, 2020)
Interferons (IFNs) form a family of cytokines with pleiotropic effects that modulate the immune response against multiple challenges like viral infections, autoimmune diseases and cancer. While numerous anti-tumor activities have been described for IFNs, IFNs have also been associated with tumor growth and progression. The effect of IFNs on apoptosis, angiogenesis, tumor cell immunogenicity and modulation of immune cells have been largely studied; however, less is known about their specific effects on cancer stem cells (CSCs). CSCs constitute a subpopulation of tumor cells endowed with stem-like properties including self-renewal, chemoresistance, tumorigenic capacity and quiescence. This rare and unique subpopulation of cells is believed to be responsible for tumor maintenance, metastatic spread and relapse. Thus, this review aims to summarize and discuss the current knowledge of the anti- and pro-CSCs effects of IFNs and also to highlight the need for further research on the interplay between IFNs and CSCs. Importantly, understanding this interplay will surely help to exploit the anti-tumor effects of IFNs, specifically those that target CSCs.